2023
DOI: 10.1038/s41597-023-02736-5
|View full text |Cite
|
Sign up to set email alerts
|

Gridded livestock density database and spatial trends for Kazakhstan

Venkatesh Kolluru,
Ranjeet John,
Sakshi Saraf
et al.

Abstract: Livestock rearing is a major source of livelihood for food and income in dryland Asia. Increasing livestock density (LSKD) affects ecosystem structure and function, amplifies the effects of climate change, and facilitates disease transmission. Significant knowledge and data gaps regarding their density, spatial distribution, and changes over time exist but have not been explored beyond the county level. This is especially true regarding the unavailability of high-resolution gridded livestock data. Hence, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Out of the 40 feature variables, 16 features have importance rankings of 10% or higher in the classification. Of course, like Kolluru V and others, we can also demonstrate how each variable helps predict the garlic distribution by plotting response curves [19]. Please refer to Supplementary Figure S1 for the variable importance for other years.…”
Section: Feature Selection Analysismentioning
confidence: 60%
“…Out of the 40 feature variables, 16 features have importance rankings of 10% or higher in the classification. Of course, like Kolluru V and others, we can also demonstrate how each variable helps predict the garlic distribution by plotting response curves [19]. Please refer to Supplementary Figure S1 for the variable importance for other years.…”
Section: Feature Selection Analysismentioning
confidence: 60%
“…The simulation results for livestock distribution in this study are consistent with the trend reported by Saizen 9 and roughly depict the areas where sheep & goats, cattle, and horses congregate in the basin, highlighting the areas with favorable conditions for livestock survival. The principal livestock of the Selenge River Basin including sheep & goats, cattle, and horses, exhibit varying distributions across certain provinces, showing a spatial clustering state, demonstrably representing genuine spatial dependence patterns inherent in livestock distribution 21 . They were mainly distributed in Khuvsgul, eastern Darkhan, and the middle-lower parts of the Khangai region upstream of the basin.…”
Section: Discussionmentioning
confidence: 99%
“…Slope and aspect were chosen because the natural environment drives the distribution of livestock mainly through the topography, and livestock tend to be distributed in plains and lower terrain areas 13 . To some extent, NPP and NDVI reflect the availability of feed biomass, which has geospatial heterogeneity and is also an important indicator of the geographical spatial distribution of livestock 21 . Precipitation and land surface temperature can reflect climatic differences in different regions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral features, phenological characteristics, polarization features, and texture features were chosen for classification. Google Earth Engine (GEE) provides an "interpretability" feature for the random forest classification algorithm, enabling the evaluation of importance scores for the feature variables involved in classification [53]. In this study, feature selection was conducted to utilize only the 30 top-performing features each year for classification (Figure 4a-e).…”
Section: Generate Training Samplesmentioning
confidence: 99%